Prenatal Diagnosis of Skeletal Dysplasia and Review of the Literature - Bashiru Babatunde Jimah; Teresa Aba Mensah; Kofi Ulzen-Appiah; Benjamin Dabo Sarkodie; Dorothea Akosua Anim; Emmanuella Amoako; Evelyn Antwiwaa Gyamfi (Hindawi Limited, 2021)
Introduction. Obstetric ultrasonography is routinely used to screen for fetal anomalies. Thanatophoric dysplasia (TD) is one of the common though rare lethal skeletal dysplasia, detected during routine ultrasound scan. TD is caused by a mutation in FGFR3 gene. Characteristic features include shortening of limbs, macrocephaly and platyspondyly. In our local setting, it is common to miss the diagnosis in the early scans due to lack of expertise of the sonographers. To the best of our knowledge, this is the first publication from Ghana. Case Presentation. We present the case of a 33-year-old woman who was referred to the facility on account of ultrasound scan report suggestive of thanatophoric dysplasia type 1 at 34 weeks of a female baby. The diagnosis was not made despite the mother being a regular antenatal attendant, until a fifth scan done at 34 weeks reported features suggestive of thanatophoric dysplasia. The ultrasound scan features included a biparietal diameter of 37weeks, femur length-24weeks, narrowed thoracic cage with hypoplastic lungs and short ribs. The liquor volume was increased with amniotic fluid index (AFI) of 38.4 cm. The femur, tibia, fibula, humerus, ulna, and radius were shortened (micromelia). The diagnosis of thanatophoric dysplasia type 1 was confirmed on autopsy. Conclusion. This report was aimed to highlight the potential contribution of ultrasound scan in the diagnosis of thanatophoric dysplasia in our setting.